Achieving Customer Intimacy Through Application Of Knowledge Management In Customer Relationship Management - Tan, Soo Leong (2008)
Competition caused by globalization and advancement in information technology has forced companies to focus on managing customer relationships, and in particular customer satisfaction, in order to remain competitive. This paper reports exploratory research based on a survey addressed to the employees of two large Malaysian organizations, a telecommunication and an automobile company.